Economic mechanism of risk management of investment projects in housing construction - Poliak, О. P. (Ways to Improve Construction Efficiency, 2020)
The article reveals some problems of risk management of investment activity of construction companies. The features of construction as a branch of production are defined, which are as follows: the long-term nature of investments in construction, a significant time gap between the moment of making investments and the moment of earning, as well as the risks of uncertainty of innovative activity. Their totality forms an extremely unstable environment for construction companies. The existing risk classifications by the following categories and features are considered: by the nature of economic activity of a construction organization (which in turn is divided into production, investment, innovation, commercial, etc. should separate relevant risks); the degree of controllability of the risks of a construction organization should be divided into unmanaged, hard-managed, well-managed; the source of risk factors should distinguish between the risks of the external and internal environment. The stages of the process of risk management of investment project activity in conditions of environmental uncertainty are presented: analysis of the external and internal environment of the investment project; determining the probability (frequency) of the event; Identifying the extent and magnitude of investment risk; determination of consequences of manifestation of risks (increase in prices of works, losses, increase of duration of construction, etc.); the choice of the necessary methods of minimizing the negative consequences, primarily aimed at reducing financial and other losses. The peculiarities of investment activity in the sphere of construction, the main risks in the implementation of investment projects are considered. There are various approaches to managing the risks of investing in the construction of construction projects. Integrated use or combination of the proposed methods and tools allows to increase the economic security of the implementation of risky investment projects, as well as to achieve and further maintain an acceptable level of risks of the investment activities of the organization.